Presence of gustatory and olfactory dysfunction in the time of the COVID-19 pandemic - Kusnik, Alexander; Weiß, Christel; Neubauer, Melanie; Huber, Bianca; Gerigk, Marlis; Miethke, Thomas; Hunter, Nicole; Rotter, Nicole; Ludwig, Sonja; Schell, Angela; Ebert, Matthias; Teufel, Andreas (BMC infectious diseases, 2021)
The unexpected outbreak of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused more than 49 million cases and an estimated 2,000,000 associated deaths worldwide. In Germany, there are currently more than 2,000,000 laboratory-confirmed coronavirus disease 2019 (COVID-19) cases including 51,800 deaths. However, regional differences also became apparent and with the second wave of infections, the detailed characterization of COVID-19 patients is crucial to early diagnosis and disruption of chains of infections.